Inscribe Lisbon with sunbeams and other sharp instruments: the city in the poetry of Fiama Hasse Pais Brandão - Fagundes, Mônica Genelhu (2022)
Having started with the proposal of observing the representation of Lisbon in the poetry of Fiama Hasse Pais Brandão, this article deviates from the referential object to the modes of its perception, and focuses on a collection of instruments that the poet uses to inscribe the cityscape in poetry. United by the aspect of sharpness and by piercing-cutting properties, these objects poetically materialize the style (a particular form of expression, but also a pointed shaft the ancients used for writing) of a spurring scripture, which Derrida recognized as an attribute of the feminine: capable of destabilizing knowledge, at the same time tearing and defending the veils of a truth that is only unveiled at a distance and as a distance.